2020
DOI: 10.1039/d0dt00124d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of anomalous conventional and spontaneous exchange bias, high coercivity in Fe doped NiCr2O4 spinel

Abstract: NiCr2−xFexO4 (x = 0 and 0.2) polycrystalline ceramics have been synthesized successfully through a simple co-precipitation technique to study the evolution of structural and magnetic properties by doping Fe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…It can be noted that the estimated T C for NiCr 1.7 Fe 0.3 O 4 nanoparticles is almost 29 K higher compared with T C ≈230 K reported for its bulk counterpart by Park et al [ 18 ] This enhancement in T C corroborates well with the enhanced T C observed for x = 0, 0.1 and 0.2 nanoparticles compared to their bulk counterparts. [ 11,12 ] Moreover, a significant increase in T C compared with the T C in NiCr 2 O 4 nanoparticles is attributed to the increase in exchange interaction between the magnetic cations occupying the A and B sites. Below T C , the irreversibility between the M FC and M ZFC is observed at irreversible temperature, T irr ≈ 244 K. The large bifurcation between the M FC and M ZFC below T irr suggests the presence of uncompensated spins accompanied by strong magnetic anisotropy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be noted that the estimated T C for NiCr 1.7 Fe 0.3 O 4 nanoparticles is almost 29 K higher compared with T C ≈230 K reported for its bulk counterpart by Park et al [ 18 ] This enhancement in T C corroborates well with the enhanced T C observed for x = 0, 0.1 and 0.2 nanoparticles compared to their bulk counterparts. [ 11,12 ] Moreover, a significant increase in T C compared with the T C in NiCr 2 O 4 nanoparticles is attributed to the increase in exchange interaction between the magnetic cations occupying the A and B sites. Below T C , the irreversibility between the M FC and M ZFC is observed at irreversible temperature, T irr ≈ 244 K. The large bifurcation between the M FC and M ZFC below T irr suggests the presence of uncompensated spins accompanied by strong magnetic anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…The development of unidirectional exchange anisotropy between the FM ordered moments at the A site and the AFM ordered moments at the B site, after partially substituting the Cr‐site with magnetic/nonmagnetic cations (i.e., Al, Fe, and Mn), has been reported to cause exchange bias phenomena in NiCr 2– x Fe x /Al/Mn x O 4 systems. [ 9,11,15 ] The exchange bias field, H EB , is estimated using the relation, HEB=|HnormalC1+HnormalC2|2 and the vertical shift in magnetization Δ M is estimated using the relation ΔM=Mmaxfalse(+70kOefalse)+Mmaxfalse(70kOefalse)2. The estimated values for H EB and Δ M are plotted as a function of temperature, as shown in Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations